Glucomanan Extract From Salak Seed (Salacca edulis Reinw.) As An Alternative Material of Making Hard Capsule Shell - Yunita, Triana; Rizky, Dharmawan Yudha; Rahajeng, Utami Putri; Fredy, Kurniawan (SPECTA Journal of Technology, 2018)
This research studied about making hard capsule shell using glucomannan extract from salak seed (Salacca edulis Reinw.). The glucomannan extracted by using etanol 96% and aqua dm. The glucomannan that had been extracted will became KGM polymer that will be used for casting the hard capsule shell using petri cup. The results obtained by smashing the seeds of salak to be smooth with meat grinder and glucomannan extraction using 2 methods with etanol 96% and isopropyl alcohol. After extracting the seeds of salak seeds, the bacon seed flour is weighed and taken some samples to obtain the best composition, resulting in a film layer on a thick capsule shell like a capsule shell in general. The result of the printing on the petri cup is still a thin layer that can not be taken, but this proves that glucomannan contained in the seeds of salak able to produce lapisal film capsule shells with the right composition.